Impact of economic factors on formal milk collection by the dairy industry in the main producing states in Brazil: a cointegration analysis - Silva Filho, Jairo Vieira da [UNESP]; Fernandes Figueira, Sergio Rangel [UNESP] (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2019)
The objective of this study was to measure the short- and long-term elasticities of the Gross Domestic Product (GDP), productivity, prices paid to producers, milk powder imports, minimum wages, and exchange ratios in milk collection between 1999 and 2016. For the measurement, the cointegration technique for data in a balanced panel was used, contemplating five states with great representativeness in the Brazilian industrial milk collection: Minas Gerais, Parana, Rio Grande do Sul, Goias, and Sao Paulo. These states corresponded to 73.3% of all formal milk collection in 2016. Results indicated that GDP, productivity, and imports impacted long-term milk collection. Productivity and GDP were the variables with the greatest long-term impact, with elasticities of 1.395 and 1.297, respectively. Minimum wages impacted milk collection to a lesser scale, -0.802; and exchange ratio and imports showed lower coefficients, that is, 0.177 and -0.078, respectively. In the short term, minimum wages was the significant variable to explain the milk collection and presented a coefficient of -0.213. The variables with the greatest impact on formal milk collection during the period analyzed were productivity, which made the production process more efficient, and variation in the Brazilian consumer's income, represented by the GDP variable, which increased the demand for dairy products.
Keywords: economy; milk; multiple regression; price